Remembering Our Founder: Hershel Shanks (1930-2021) - Alexander, Elizabeth (The Biblical archaeology review, 2021)
The Biblical Archaeology Society remembers the life and achievements of Biblical Archaeology Review’s founder and Editor Emeritus, Hershel Shanks, who passed away February 5, 2021, at the age of 90.